К ФАУНЕ ТЛЕЙ (Homoptera, Aphididae) ТУГАЙНЫХ БИОТОПОВ РЕКИ СЫРДАРЬИ (Experimental biology, 2009)
Kadyrbekov Rustem Kh. About fauna of Aphids (Homoptera, Aphididae) of the gallery forests of Syrdariya river 71 species from the 34 genera, Eriosomatinae (5 species), Chaitophorinae (8), Saltusaphidinae (1), Callaphidinae (1), Pterocommatinae (3) and Aphidinae (53) subfamilies of the Aphididae family are exposed in the collection of the Institute of Zoology (Almaty) from gallery forests of the Syrdariya river. The annotated list of the revealed species with the indication of biotopic specialization, host plants and places of localization on them, domination, distribution insideexamined region and types of area is resulted. Majority of the species inhabits in the some biotops of gallery forests. Aphids fauna of the gallery forests of Syrdariya river is very original. Per cent of the local northern turanian species is the rather elevated (16,9%).
Keywords: Chaitophorinae; Saltusaphidinae; Eriosomatinae